2015
DOI: 10.1016/j.bpj.2015.03.029
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Reduces Tension and Increases Undulations in Simulations of Small Unilamellar Vesicles

Abstract: Using coarse-grained molecular dynamics simulations we have explored the effect of a-Synuclein (aSyn) on the structural and mechanical properties of small unilamellar vesicles in the fluid-phase. The study is motivated by observations that a high density of membrane-bound aSyn inhibits the fusion of synthetic small unilamellar vesicles. By combining three-dimensional pressure tensor calculations with our recently developed spherical harmonics fluctuation analysis approach, we show a reduction in membrane surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…It has been suggested that the extended and broken-helix conformations could interconvert (Georgieva et al, 2010; Robotta et al, 2011; Lokappa and Ulmer, 2011), potentially in a lipid-dependent fashion (Borbat et al, 2006; Middleton and Rhoades, 2010). Outside of coarse-grained simulations (Braun et al, 2012; Braun and Sachs, 2015), this conformational diversity had not been sampled, and presented a prime candidate for using the HMMM model to investigate the specific lipid interactions that determine the membrane-bound structure of α S.…”
Section: Applications Of Hmmm To Membrane-associated Phenomenamentioning
confidence: 99%
“…It has been suggested that the extended and broken-helix conformations could interconvert (Georgieva et al, 2010; Robotta et al, 2011; Lokappa and Ulmer, 2011), potentially in a lipid-dependent fashion (Borbat et al, 2006; Middleton and Rhoades, 2010). Outside of coarse-grained simulations (Braun et al, 2012; Braun and Sachs, 2015), this conformational diversity had not been sampled, and presented a prime candidate for using the HMMM model to investigate the specific lipid interactions that determine the membrane-bound structure of α S.…”
Section: Applications Of Hmmm To Membrane-associated Phenomenamentioning
confidence: 99%
“…In the more challenging case of small vesicles, we explore neutron spin echo (NSE) [6163], and atomic force microscopy (AFM) experiments [6469]. Finally, we describe the most recent efforts, including our own, to accurately capture bending rigidity from simulations of fluctuating membranes, both in flat bilayers and small vesicles [7074]. …”
Section: Introductionmentioning
confidence: 99%
“…Interconversion between these two states had been hypothesized [36, 148150], with special emphasis on the role of specific lipid interactions in regulating the equilibrium between the two populations [36, 151, 152]. Coarse-grained simulations sampled this conformational diversity in part [153, 154], but due to their resolution limitations could not identify specific interactions that anionic membranes might disrupt to allow this transition to take place.…”
Section: Lipid-specific Membrane-induced Conformational Change In mentioning
confidence: 99%